PsycEXTRA Dataset 2014
DOI: 10.1037/e565622014-001
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Disability and Intimate Partner Violence in the United States

Abstract: Purpose-Prior research has shown that people with disabilities are at greater risk of intimate partner violence (IPV) victimization. This study seeks to examine the link between disability and IPV in a nationally representative sample of U.S. women and men. Also, by establishing that disability preceded recent IPV victimization, this study allows for a more thorough understanding of whether people with disabilities are at greater risk of victimization subsequent to having a disability. Methods-Data were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 5 publications
4
94
0
1
Order By: Relevance
“…8 Further examining the type, frequency, and severity of youth SV victimization may provide key information in understanding gendered disparities that prevalence estimates do not provide. 9 …”
Section: Discussionmentioning
confidence: 99%
“…8 Further examining the type, frequency, and severity of youth SV victimization may provide key information in understanding gendered disparities that prevalence estimates do not provide. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Research has consistently found that low SES, including poverty, is associated with higher levels of both IPV and SV victimization. 1,2 Though associated with poverty, two indicators of economic insecurity, food and housing insecurity, have been identified as conceptually distinct social determinants of health. 3,4 Anderson 5 defined food insecurity as existing “whenever the availability of nutritionally adequate and safe foods or the ability to acquire acceptable foods in socially acceptable ways is limited or uncertain.” Food insecurity has been operationalized in the literature as either concern about not having enough food, food not lasting, needing to cut or skip meals, going hungry, or some combination of these.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging body of literature on bisexual women suggests that they experience distinct forms of oppression (Brewster & Moradi, 2010; Dyar, Feinstein, & London, 2014; Eliason, 1997; Israel & Mohr, 2004; Mohr & Rochlen, 1999) and fare worse than lesbian women on several physical and mental health metrics including cardiovascular disease risk (Conron, Mimiaga, & Landers, 2010; Dilley, Simmons, Boysun, Pizacani, & Stark, 2010), anxiety (Jorm, Korten, Rodgers, Jacomb, & Christensen, 2002; Kerr, Santurri, & Peters, 2013), depression (Jorm et al, 2002; Kerr et al, 2013; Pyra et al, 2014), suicidality (Conron et al, 2010; Pompili et al, 2014), and violence and victimization (Breiding, Chen, & Black, 2010). These disparities highlight the need for more investigation into the unique experiences of bisexual women.…”
mentioning
confidence: 99%